2016
DOI: 10.1155/2016/3607924
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Assessment of Antibacterial Activities of Ruthenium(III) Mixed Ligand Complexes Containing 1,10-Phenanthroline and Guanide

Abstract: In this work, two complexes of ruthenium(III) ([Ru(phen)2Cl2]Cl·2H2O and [Ru(phen)2(G)Cl]2Cl·H2O) were synthesized from 1,10-phenanthroline alone as well as from both 1,10-phenanthroline and guanide. The synthesis was checked using halide test, conductance measurement, and spectroscopic (ICP-OES, FTIR, and UV/Vis) analysis. Their in vitro antibacterial activities were also investigated on two Gram-positive (Staphylococcus aureus (S. aureus) and methicillin resistant Staphylococcus aureus (MRSA)) and two Gram-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Among above mentioned metal complexes, ruthenium compounds are promising for medicinal and biotechnological applications as they present unique properties: (i) multiple oxidation states (II, III and IV), which are accessible in physiological conditions; (ii) favorable ligand‐exchange kinetics; (iii) multiple cytotoxic routes involving the competing processes of extracellular protein binding (active transport), due to the ability to mimic iron and cellular uptake (passive diffusion); (iv) different molecular pathways involving the concurrent intercalation and covalent binding with DNA and binding to extracellular sites inducing conformational modifications; (v) numerous synthetic opportunities for modifying the biological activity which depends on both the oxidation state of the metal center and the associated ligands surrounding it. Taking into consideration that ruthenium‐based molecules are studied as promising compounds from biological perspectives as well as the ferrocene‐substituted carborane ruthenium(II)‐arene complex exhibits promising antibiofilm activity, we have decided to investigate the ruthenium compounds in different oxidation states as potential antibiofilm agents.…”
Section: Introductionmentioning
confidence: 99%
“…Among above mentioned metal complexes, ruthenium compounds are promising for medicinal and biotechnological applications as they present unique properties: (i) multiple oxidation states (II, III and IV), which are accessible in physiological conditions; (ii) favorable ligand‐exchange kinetics; (iii) multiple cytotoxic routes involving the competing processes of extracellular protein binding (active transport), due to the ability to mimic iron and cellular uptake (passive diffusion); (iv) different molecular pathways involving the concurrent intercalation and covalent binding with DNA and binding to extracellular sites inducing conformational modifications; (v) numerous synthetic opportunities for modifying the biological activity which depends on both the oxidation state of the metal center and the associated ligands surrounding it. Taking into consideration that ruthenium‐based molecules are studied as promising compounds from biological perspectives as well as the ferrocene‐substituted carborane ruthenium(II)‐arene complex exhibits promising antibiofilm activity, we have decided to investigate the ruthenium compounds in different oxidation states as potential antibiofilm agents.…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, the synthesis of new metal complexes and evaluation of their antibacterial activity have been considered by the global community as part of the solution (Saha et al, 2009;Rafique et al, 2010). Based on this, a good number of mononuclear (Ghatole et al, 2012;Pasdar et al, 2015;Atakilt Abebe and Tizazu Hailemariam, 2016;Atakilt Abebe and Getinet Tamiru, 2018), binuclear (Patel et al, 2009;Krishna et al, 2013;Gurumoorthy et al, 2014;Panda et al, 2015;) and metal mixed-ligand complexes have been reported in the literature. In particular, Co (II) containing mixed ligand complexes appeared promising in solving the aforementioned problems (Patel et al, 2009;Chang et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
“…Some of these have been shown to exhibit anti-biotic and -cancer activities [5] [6]. In this regard, extensive applications have been found for 1,10-phenanthroline, a bidentate ligand that forms very stable chelates with many first-row transition metals [7].…”
Section: Introductionmentioning
confidence: 99%
“…The ideally placed nitrogen atoms, of this molecule, along with its rigid planar structure, hydrophobic, electron-poor heteroaromatic, and π-acidic properties, cooperatively make 1,10-phenanthroline a classic chelating ligand, for mixed ligand complexes [7].…”
Section: Introductionmentioning
confidence: 99%